Spontaneous housing in Sana’a, Yemen – Case studies - Al-Ansi, Nashwan Abdoulkarim; Wan Badaruzzaman, Wan Hamidon; Wahid, Julaihi; Md. Darus, Zuhairuse (2008)
The influx of rural population after the Yemen’s revolution in the early sixties, the union between North and South Yemen in the early nineties, and the returning of the war veterans after the second Gulf war in 1991 have contributed to many spontaneous and unorganized housing settlement areas that are not equipped with basic necessities. These settlements have created a negative impact on the social, economical, and the environmental conditions of the urban areas. The spontaneous housing settlements are considered as the most deteriorating urban communities due to insufficient infrastructure services available to the people. This study attempts to focus on the spontaneous settlement of Madbah (City by Night) and Sawad Hizyaz housing (Union Street) in Yemen. They are good examples that represent the status of spontaneous housing in Sana’a and other cities in Yemen. The discussion will delve into the nature of the housing situation and uncovered the problems and potentials of the dwellers in these living environments. The study relies on the data which has been collected via questionnaires, interviews, field visits, personal observations and photographs. It is discovered that the areas under study was completely spontaneous in nature; lacking in basic necessities, infrastructure services and public utilities as required by the dwellers. Based on the conclusions, the study produced few suggestions and recommendations on how to improve the living environment of the areas under investigation, and these findings will be used to assist the spontaneous housing in other areas of Yemen.